APAKAH WPA/WPA2 BENAR-BENAR AMAN? DEKRIPSI PAKET DATA TERENKRIPSI PADA WPA/WPA2 - Siti Zaim (Seminar Nasional Informatika (SEMNASIF), 2015)
WPA2 is considered as the most secure configuration for  Wi-Fi network and widely used to secure private and enterprise Wi-Fi network. The early protocol, WEP uses RC4 stream cipher algorithm without key management and WPA uses Temporal Key Integrity Protocol (TKIP) with hash function to scramble the key, while WPA2 use Advanced Encryption Standard (AES) algorithm to encrypt data. One of parameter for generate encryption key in WPA/WPA2 is preshared key. In 2008, Beck and Tews have proposed a practical attack on WPA by exploiting the preshared key. In this paper, we propose exploitation preshared key to decrypt WPA/WPA2 encrypted data. As a result we propose some prevention and anticipation methods from users that utilize wireless network to protecting data during transmission in wireless network with WPA/WPA2 protocol.